Unit-Area Soil, Soil C and Nutrient Fluxes Decrease in the Downstream Direction of a River Basin: A Case of Thukela River Basin, South Africa - Mutema , Macdex; Chaplot , Vincent (Emerging Issues in Environment, Geography and Earth Science Vol. 3, 2023)
The objective of the study was to elucidate the evolution of runoff, sediment, soil C and nutrient fluxes using hierarchically nested catchments (micro-catchment with plots in it, sub-catchment, catchment, sub-basin and basin) over four years in the Thukela River basin, which is located in the east of South Africa. Although the effects of soil erosion, and the associated soil carbon (C) and nutrients, on the environment, are well known, there is still no consensus on how the fluxes evolve in a downstream direction within river basins, due to a lack of quality data in addition to many other reasons. The results of the study showed a general decrease of the unit-area runoff, soil, soil organic C and nutrient losses as spatial area increased from the plot to the basin scale. The trends of the fluxes were interpreted in terms of possible processes involved and the major controlling factors. Deposition, infiltration and mineralization were regarded as the key processes driving the observed trends. The intra-basin peaks were attributed to underground water inputs, emerging land uses and settlements. Restoration of vegetation and gully stabilization was recommended to combat soil, C and nutrient losses.